2000
DOI: 10.1111/j.1749-7345.2000.tb00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative Abundance and Species Composition of Gram‐Negative, Aerobic Bacteria Associated with the Gut of Juvenile White Shrimp Litopenaeus vannamei Reared in Oligotrophic Well Water and Eutrophic Pond Water

Abstract: Gut bacteria may contribute significantly to the growth and survival of cultured shrimp, although little is known about factors that affect bacterial community structure in shrimp guts. The objective of this study was to determine the abundance and species composition of gut bacteria in juvenile white shrimp Litopenaeus vannamei reared in two different environments. Eight 120‐L tanks were stocked at a density of 8 shrimphank. Two treatments were tested for 10 d and consisted of tanks receiving flow‐through wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…However, bacterial abundances in the gut and feces of P. vannamei were of the same order of magnitude as in Moss et al (2000); they estimated 2 Â 10 10 CFU g À1 gut tissue in P. vannamei. Comparisons of our direct bacterial counts in shrimp feces with published values are difficult because previous studies used culture-based methods.…”
Section: Bacterial Abundance Production and Turnover Ratesmentioning
confidence: 80%
“…However, bacterial abundances in the gut and feces of P. vannamei were of the same order of magnitude as in Moss et al (2000); they estimated 2 Â 10 10 CFU g À1 gut tissue in P. vannamei. Comparisons of our direct bacterial counts in shrimp feces with published values are difficult because previous studies used culture-based methods.…”
Section: Bacterial Abundance Production and Turnover Ratesmentioning
confidence: 80%
“…However, the current knowledge on the intestinal microbiota of crustaceans is still very limited and the majority of studies conducted so far have used conventional culture based microbiological methods, therefore providing incomplete information (Dempsey et al 1989;Harris 1993;Moss et al 2000;Oxley et al 2002). Only a limited number of studies have used molecular methods to describe the microbiota of shrimps (Li P. et al 2007;Johnson et al 2008;Castex 2009;Liu et al 2011a) or other crustaceans (Battison et al 2008;Daniels et al 2010).…”
Section: Lactic Acid Bacteria (Lab)mentioning
confidence: 99%
“…It is accepted that crustaceans have a less developed GI microbiota than fish and that the microbiota would be predominately transient in the foregut and the hindgut regions. Bacterial concentration and composition are thus likely to be influenced by a variety of parameters, such as the culture system, temperature, bacterial communities of the culture medium, feeding, moulting, intestinal transit and defecation (Moss et al 2000). Also while most research has focused on bacteria that are able to attach to intestinal mucus, transient bacteria have also been demonstrated to exert beneficial effects in crustaceans (Castex et al 2008;2009;2010).…”
Section: Competition For Nutrients and Adhesion Sitesmentioning
confidence: 99%
“…Vibrios also belong to the normal microflora of the shrimp Litopenaeus vannamei (Vandenberghe et al, 1999). Moss et al (2000) reported that Vibrio and Aeromonas species comprised up to 85 % [about 10 9 c.f.u. (g gut tissue)…”
mentioning
confidence: 99%